Precision of three-dimensional stereo-photogrammetry (3dMD™) in anthropometry of the auricle and its application in microtia reconstruction. Issue 5 (May 2015) - Chen, Zung-Chung; Albdour, Mohammad Nayef; Lizardo, Jesus Ablaza; Chen, Ying-An; Chen, Philip Kuo-Ting
Summary Background The advent of three-dimensional stereo-photogrammetry in recent years has vastly helped the craniomaxillofacial field improve in terms of preoperative and intraoperative decision making. With regard to the auricle though, there is paucity of research as to the application of this promising technology. Methods A total of 20 normal adult ears were included in this study. Thirteen anthropometric measurements were taken, twice by two plastic surgeons using direct measurement (DM) and through images captured via 3dMD™. The purpose was to compare the reliability of measurements involving the two instruments. Results The overall mean absolute differences (MADs) of all ear anthropometries of DM and 3dMD™ were 0.52 mm (range: 0.28–0.72 mm) and 0.27 mm (range: 0.15–0.53 mm), respectively, and the grand mean relative error magnitudes (REMs) were 2.85% (range: 1.01–5.99%) and 1.57% (range: 0.48–3.62%), respectively, across observers. Thus, the precision of all ear anthropometries across observers was high in both methods, but the precision of 3dMD was better than DM irrespective of observers. In addition, the MADs were less than a millimeter across all measurements. Conclusion The application of three-dimensional technology in microtia surgery for both template production and soft tissue analysis leads to improved planning and satisfactory results with fewer complications. We believe that with further refinement and enhancement, the use of this innovation will pave the way for prefabricated, individualized autologous or biocompatible alloplastic implantable frameworks based on an accurate mirror image of each patient's normal ear in unilateral cases and in bilateral cases, appropriately sized.